Extração de compostos bioativos das folhas de espinheira santa (Monteverdia aquifolia) via tecnologia supercrítica utilizando cossolventes e extração assistida por ultrassom - Alves, Tales Prado (2021)
Espinheira santa (Monteverdia aquifolia) is a medicinal plant, native from South America, and its extracts present in their composition bioactive substances, coadjuvants in the treatment of various diseases. Usually, conventional methods are applied to obtain its extracts, which most of the time are expensive and deleterious to the bioactive compounds. In this context, the present research project aims at investigating different methods of obtention of the M. aquifolia leaves extract through Soxhlet (SOX), pressurized-liquid (PLE), ultrasound-assisted (UAE), supercritical CO2 (SFE), and SFE with cosolvents extractions, evaluating the yield and the quality of the extracts obtained, regarding their chemical composition, total phenolics content (TPC), and antioxidant activity. The PLE (30 min and 100 bar) and SOX (360 min) were performed at temperatures 40, 50, and 60 °C and in the boiling temperatures of the solvent’s ethanol, ethyl acetate, and n-hexane, respectively. In the PLE, the highest yields were 5.29%, 3.13%, and 2.05% with ethanol, ethyl acetate, and n-hexane, respectively, obtained at 60 °C. SOX conventional technique was effective when performed with ethanol, reaching a yield of 8.30% in weight. These techniques evidenced the affinity of the compounds by polar solvents and improvement of the yields with temperature increase. From these data, ethanol was selected to continue with UAE, in which a Box-Behnken experimental design was used to investigate the variables temperature (40, 50, and 60 °C), sonication amplitude (20, 50, and 80%), and solvent/leaf ratio (10, 15, and 20 mL g-1) for a total period of 30 min. The combination of the adopted parameters (50 °C, amplitude 80%, and solvent/leaf ratio 20 mL g-1) resulted in a maximum yield of 6.57% in weight, obtained at a reduced time, temperature, and solvent volume when compared to SOX and PLE techniques. In the SFE-CO2, the variables investigated were pressure (200, 250, and 300 bar), temperature (40, 50, and 60 oC), and flow (2, 4, and 6 mL min-1), following a experimental design in a total time of 100 min. The highest yield of extract was 1.13%, obtained in the condition 50 °C, 300 bar, and 6 mL min-1. In this condition, the effects of the addition of 1, 3, and 5% V V-1 of the cosolvents ethanol and ethyl acetate were investigated, reaching the highest yields 1.13% and 1.06% in weight, respectively, in the concentration 5%, but not higher than the highest yield obtained with pure CO2. The adjustments of the Sovová model to the kinetics curves of SFE showed a high level of accuracy. The TPC estimate was higher in the ethanolic extracts in UAE (402.33 mg EAG gext-1), followed by PLE (325 mg EAG gext-1), SOX (237.40 mg EAG gext-1), and SFE (18.21 mg EAG gext-1). The highest antioxidant activity determined by the DPPH method was observed in the ethanolic extract obtained in the PLE (1014.01 μmol TEQ gext-1) and by the FRAP method the ethanol extract obtained by UAE (4237.60 μmol Fe2+ gext-1). The characterization of the chemical composition revealed the presence of compounds of great interest, being the majority squalene, vitamin E, friedelin, and friedelanol. The quantification of vitamin E and friedelin was higher in the extracts obtained in the PLE with ethyl acetate. Generally, the unconventional methods were superior to the conventional method, presenting improved chemical composition, TPC, and antioxidant activities.